The legal framework of competition and the prevention of monopolistic practices: Analytical study in light of the laws in Palestine - صالح نعيم جميل (Journal of Legal Sciences, 2019)
This research aims at addressing the legal framework of competition and the prevention of monopolistic practices “analytical study in light of the laws in force in Palestine” by focusing on comparing the legal concept of competition and monopoly prevention, the international and national efforts to encourage competition and prevent monopoly, and addressing some of the practices associated with it. The importance of developing policies that protect competition and prevent monopoly is a priority of competent authorities due to its positive effects on improving the economic, trade and investment environment and promoting SMEs by convincing the competent authorities to strengthen the integration and coordination between the Palestinian economic and commercial legislation system protecting the market as well as the consumer. The legislative framework governing competition in Palestine was also addressed through some of the legal texts of some of the laws. It is worth noting that the existence of the different legal provisions of the Palestinian legislation does not meet the purpose an independent body requires to adopt a Palestinian law that encourages competition and prevents monopolistic practices. Such a body that will implement the required law similar to some of the comparative laws.